Regional Unemployment Rates and Total Economic Growth in Canada, 1953-1968 - Donner, Arthur (Relations industrielles / Industrial Relations, 1971)
In this article the author tests the hypothesis that the process of general economic growth in Canada has an unequal impact on regional economic activity.